Die Rolle der Elaboration beim Verstehen und Behalten von fremdsprachigen Texten - Domas, Oskar (Wydawnictwo Naukowe UAM, 1997)
Topic of the article is the influence of the process of elaboration, as one of thinking processes taking place during text perception, on understanding and memorizing the text. On the basis of the topic literature, the author analyses psycholinguistic benefits of elaboration, explains the way elaboration causes better comprehension and memorizing. He presents the possibilities of using elaboration during work with a foreign language text. In the light of the results of the experiment conducted by the author, it becomes once again clear that the success of dydactic process is to a large extent dependant on the person of a teacherk, in particular on the techniques and strategies by them in text work.